2020
DOI: 10.12717/dr.2020.24.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expressions of Aquaporin Subtypes in Female Reproductive Tract of Mice

Abstract: Although many aquaporin (AQP) transcripts have been demonstrated to express in the female reproductive tract, the defined localizations and functions of AQP subtype proteins remain unclear. In this study, we investigated the expression of AQP1, AQP3, AQP5, AQP6, and AQP9 proteins in female reproductive tract of mouse and characterized their precise localizations at the cellular and subcellular levels. Immunofluorescence analyses for AQP1, AQP3, AQP6, and AQP9 showed that these proteins were abundantly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This suggests the involvement of other factors in the regulation of water transport through the epithelium, such as the water channel aquaporins (e.g. AQP1 , AQP3 , AQP6 and AQP9 in the oviduct) and cystic fibrosis transmembrane conductance regulator ( CFTR ) (Im et al 2020 ). Further investigations are warranted to assess the activities of ion and water channels at the protein level to validate the mechanisms governing the OFS volume.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the involvement of other factors in the regulation of water transport through the epithelium, such as the water channel aquaporins (e.g. AQP1 , AQP3 , AQP6 and AQP9 in the oviduct) and cystic fibrosis transmembrane conductance regulator ( CFTR ) (Im et al 2020 ). Further investigations are warranted to assess the activities of ion and water channels at the protein level to validate the mechanisms governing the OFS volume.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase‐3 and caspase‐9 primarily act as apoptosis performers and are markers of ovarian granulocyte apoptosis (Araya et al, 2021). AQP3 affects cell proliferation and apoptosis by regulating osmotic pressure inside and outside the cell membrane (Im et al, 2020). Therefore, we consider that AQP3 overexpression increased the apoptosis rate of ovarian granulosa cells at 24 h following AQP3 transfection.…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing revealed that KIF26B , AQP3 , SPIB and Novel00378 were the common DEGs in the ovarian tissues of dairy goats treated with repeated FSH‐ or eCG‐mediated ES treatment. Among the common genes, AQP3 functions as a hydrophilic membrane protein in mammalian ovarian cells (Im et al, 2020). By participating in the regulation of sperm volume, AQP3 can prevent cell swelling caused by low osmotic pressure when sperms enter the vagina (Qi & En‐Kui, 2011), optimizing the ability of sperms to bind to oocytes (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, most genes related to ovarian reserve and primordial follicle reactivation were not altered; however, a larger number of dysregulated genes were identified. Some studies have reported that AQP1, AQP3, and AQP9 present in the ovarian follicle corpus luteum contribute to the rapid growth of follicles during folliculogenesis, follicular fluid accumulation, and nutrient supply to granulosa cells and oocytes (Lm et al, 2020). Sales et al (2016) found that mRNA levels of AQP3 and AQP9 in bovine ovaries were downregulated, following vitrification, which can cause AQP3 upregulation and AQP1 mRNA downregulation in human ovary tissues, suggesting that AQP1 and AQP3 may have different functional mechanisms for human follicle growth.…”
Section: Figurementioning
confidence: 99%